Academic Stress and Achievement Motivation as Associated Factors of Burnout Among Vocational High School Students: A Cross-Sectional Study - Suhardiningsih, AV Sri; Sustrami, Dya; Rustini, Sri Anik; Widianto, Ardin Putra (Journal of Applied Nursing and Health, 2026)
Background: Final-year vocational high school students are exposed to substantial academic and practical training demands that may be associated with burnout. Within the Job Demands–Resources (JD-R) framework, academic stress is an academic demand, whereas achievement motivation is a personal resource. However, limited studies have simultaneously examined the relationships among achievement motivation, academic stress, and Burnout among vocational high school students. Therefore, this study aimed to analyze these relationships using the JD-R framework. Methods: A quantitative cross-sectional study was conducted among 115 twelfth-grade vocational high school students selected through simple random sampling. Data were collected using the AMI, ESSA, and MBI-SS questionnaires. Scores were categorized for descriptive purposes, and associations among variables were analyzed using Spearman’s rank correlation test. Ethical approval was obtained before data collection. Results: Most participants reported moderate achievement motivation (73.9%) and moderate Burnout (62.6%), whereas 53.9% experienced high academic stress. Spearman’s correlation analysis revealed a significant negative association between achievement motivation and Burnout (r = −0.602, p < 0.001). In contrast, academic stress was significantly positively associated with Burnout (r = 0.275, p = 0.003). Conclusion: Higher achievement motivation is linked to lower Burnout, while higher academic stress is linked to higher Burnout among final-year vocational students. Improving motivation and managing stress may help reduce Burnout.